SURGICAL NUTRITION - Danny Kurniawan Darianto; M. Affandi (Faculty of Dentistry, Universitas Indonesia, 2015)
A patient undergoing surgery faces great physiologic and psychologic stress. so nutritional demands are greatly increased during this period and deficiencies can easily develop. If these deficiencies are allowed to develop and are not in screening, serious malnutrition and clinical problem can occur. Therefore careful attention must be given to a patient's nutritional status in preparation of surgery, as well as to the individual nutritional needs. If these needs are met, complications are less likely developing. Natural resources provide for rapid recovery. Proper nutrition can speed healing in surgical patients with major trauma, severe malnutition, burns, and other severe illnesses. New techniques for tube feeding, intravenous nutrition for patients with serious weight loss due to gastrointestinal disorders, and use of supplements can hasten wound healing and shorten recovery times.